Gait Characteristics Associated with Walking Speed Decline in Older Adults: Results from the Baltimore Longitudinal Study of Aging - Jerome, Gerald J (Arch Gerontol Geriatr, 2015)
BACKGROUND: Understanding the mechanisms that contribute to walking speed decline can provide needed insight for developing targeted interventions to reduce the rate and likelihood of decline. OBJECTIVE: Examine the association between gait characteristics and walking speed decline in older adults. METHODS: Participants in the Baltimore Longitudinal Study of Aging aged 60 to 89 were evaluated in the gait laboratory which used a three dimensional motion capture system and force platforms to assess cadence, stride length, stride width, percent of gait cycle in double stance, anterior-posterior mechanical work expenditure (MWE), and medial-lateral MWE. Usual walking speed was assessed over 6 meters at baseline and follow-up. Gait characteristics associated with meaningful decline (decline ≥ 0.05 m/s/y) in walking speed were evaluated by logistic regression adjusted for age, sex, race, height, weight, initial walking speed and follow-up time. RESULTS: Among 362 participants, the average age was 72.4 (SD=8.1) years, 51% were female, 27% were black and 23% were identified has having meaningful decline in usual walking speed with an average follow-up time of 3.2 (1.1) years. In the fully adjusted model, faster cadence [ORadj=0.65 95% CI (0.43,0.97)] and longer strides [ORadj=0.87 95% CI (0.83,0.91)] were associated with lower odds of decline. However age [ORadj=1.04 95% CI (0.99,1.10)] was not associated with decline when controlling for gait characteristics and other demographics. CONCLUSION: A sizable proportion of healthy older adults experienced walking speed decline over an average of 3 years. Longer stride and faster cadence were protective against meaningful decline in usual walking speed.